The rise of industrial America a people's history of the post-Reconstruction era. - Smith, Page 1917- (McGraw-Hill, 1984)
A history of America between 1876 and 1901 focuses on the influence of new scientific ideas, such as evolution, and the growing conflicts between business and labor.